Analisis Kelangkaan Minyak Goreng Terhadap Masyarakat Medan - Kusnadi, Hafidah Ayu; Anggraini, Sheila; Batubara, Maryam (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
This study aims to determine how people's attitudes towards the scarcity of cooking oil in the city of Medan. Cooking oil is one of the nine basic ingredients that have an important role for the people of Indonesia and also for the Indonesian economy. The city of Medan is one of the big cities which of course also needs cooking oil for consumption needs for household use or for trading. The conditions that occurred during the economic crisis a few years ago, when there was a shortage of cooking oil in the local market, showed the importance of cooking oil as a daily necessity. The results and conclusions are that the causes of the increase in cooking oil prices include hoarding, smuggling of cooking oil, and public panic buying. The government's actions are to make a policy regarding cooking oil at one price per liter, establish a Food Task Force Team, create a complaint hot line, and provide a budget for subsidizing cooking oil prices. The factors that influence consumer behavior in buying cooking oil are price, income, daily needs and easy to obtain.